2011
DOI: 10.1002/anie.201101274
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis of Colloidal Inorganic Nanocrystals

Abstract: Colloidal inorganic nanocrystals stand out as an important class of advanced nanomaterials owing to the flexibility with which their physical-chemical properties can be controlled through size, shape, and compositional engineering in the synthesis stage and the versatility with which they can be implemented into technological applications in fields as diverse as optoelectronics, energy conversion/production, catalysis, and biomedicine. The use of microwave irradiation as a non-classical energy source has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
561
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(566 citation statements)
references
References 409 publications
(455 reference statements)
5
561
0
Order By: Relevance
“…This technology makes use of two heating mechanisms namely dipolar polarization and ionic conduction. The dipoles in the reaction chamber are involved in the polarization effect, while the charged particles in a reaction chamber (usually ions) contribute to ionic conduction effect [35]. When reaction chamber is irradiated, the dipoles or ions in the sample align themselves in the direction of applied electric field.…”
Section: Resultsmentioning
confidence: 99%
“…This technology makes use of two heating mechanisms namely dipolar polarization and ionic conduction. The dipoles in the reaction chamber are involved in the polarization effect, while the charged particles in a reaction chamber (usually ions) contribute to ionic conduction effect [35]. When reaction chamber is irradiated, the dipoles or ions in the sample align themselves in the direction of applied electric field.…”
Section: Resultsmentioning
confidence: 99%
“…[42][43][44][45][46] Because of such properties, nanorods are potential candidates for practical applications as ozone gas sensors.…”
Section: -33mentioning
confidence: 99%
“…16,17 In particular, Kappe et al 18 reported a critical assessment of the specic role of microwave irradiation in the synthesis of ZnO micro-and nanostructured materials. This synthetic procedure provides an economically viable route for applications but also opens a new avenue to study the structural kinetics and chemistry of semiconductors and nanocrystals.…”
mentioning
confidence: 99%
“…The MAH method results in micro-or nanocrystals with high purity and crystallinities at lower temperatures than conventional heating methods. [15][16][17][18][19] An elemental analysis reveals that the products contain only Zn and O atoms (see Fig. 2(c)).…”
mentioning
confidence: 99%